Structural Modeling of the Relationship Between Organizational Factors and Negative Job Outcomes Mediated by Job Characteristics Among Teachers in Urmia - Kasraie , Shokoufeh; Yari Haj Ataloo , Jahangir; Maleki Avarsin, Sadegh; Habibi , Hamdullah (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective:  The present study aims to structurally model the relationship between organizational factors and negative job outcomes mediated by job characteristics among teachers in Urmia County.Methodology: This correlational research involved a statistical population of all teachers in Urmia County, totaling 10,000 individuals. The research sample, based on the Morgan table, comprised 373 individuals, selected using proportional stratified random sampling. To measure the variables, questionnaires on organizational support (Eisenberger, 1997), organizational identity (Cheney, 1983), job stagnation (Judith Bardwick, 1988), intention to leave the job (Mobley-Horner, 1978; Lyons, 1971), organizational silence (Vakola & Bouradas, 2005), job autonomy (Jang, 1995), and job security (Nissi, 2000) were used. The content validity of the questionnaires was confirmed by experts and advisors, and the reliability of the questionnaires was estimated to be 0.953, 0.984, 0.968, 0.972, 0.992, 0.918, and 0.980, respectively. In this study, the PLS method was used with the help of Smart PLS 3.2.9 software to fit the conceptual research model and test the hypotheses.Findings: The results indicate that organizational factors (organizational identity and organizational support) have a significant inverse relationship with negative job outcomes (organizational silence, job stagnation, and intention to leave the job). Thus, there is an indirect and significant inverse relationship between the organizational factors of teachers (organizational identity and organizational support) and negative job outcomes (organizational silence, job stagnation, and intention to leave the job) mediated by job characteristics (job autonomy and job security) among teachers in Urmia County.Conclusion: Thus, with an increase in organizational identity and organizational support, teachers' job autonomy and sense of job security increase, which in turn reduces their negative job outcomes, namely intention to leave the job, job stagnation, and organizational silence.